High-maintenance-dose clopidogrel in patients undergoing percutaneous coronary intervention: a systematic review and meta-analysis. - Yu Chen; Yachen Zhang; Yong Tang; Xiaohong Huang; Yuquan Xie (PLoS ONE)
Background Despite routine use of clopidogrel, adverse cardiovascular events recur among some patients undergoing percutaneous coronary intervention (PCI). To optimize antiplatelet therapies, we performed a meta-analysis to quantify the efficacy of high versus standard-maintenance-dose clopidogrel in these patients. Methods Randomized controlled trials (RCTs) comparing high (>75 mg) and standard maintenance doses of clopidogrel in patients undergoing PCI were included. The primary efficacy and safety end-points were major adverse cardiovascular/cerebrovascular events (MACE/MACCE) and major bleeding. The secondary end-points were other ischemic and bleeding adverse effects. The pooled odds ratio (OR) for each outcome was estimated. Results 14 RCTs with 4424 patients were included. Compared with standard-maintenance-dose clopidogrel, high-maintenance-dose clopidogrel significantly reduced the incidence of MACE/MACCE (OR 0.60; 95% CI 0.43 to 0.83), stent thrombosis (OR 0.56; 95% CI 0.32 to 0.99) and target vessel revascularization (OR 0.38; 95% CI 0.20 to 0.74), without significant decrease of the risk of cardiovascular death (OR 0.92; 95% CI 0.74 to 1.13) and myocardial infarction (OR 0.83; 95% CI 0.51 to 1.33). For safety outcomes, it did not significantly increase the risk of major bleeding (OR 0.73; 95% CI 0.41 to 1.32), minor bleeding (OR 1.29; 95% CI 1.00 to 1.66) and any bleeding (OR 1.14; 95% CI 0.91 to 1.43). Conclusion High-maintenance-dose clopidogrel reduces the recurrence of most ischemic events in patients post-PCI without increasing the risk of bleeding complications.